Subverting the Authority of Western Discourse in Postcolonial Ethnographic Film - Borjan, Etami (2011)
The aim of the lecture is to question the role of contemporary postcolonial ethnographic film within the context of Film Studies and visual anthropology. The aim of my lecture is to discuss the status of ethnographic film today and to question the relevance of the traditional paradigms of visual anthropology. Through the analysis of the recent film production and the ways in which indigenous filmmakers use film and mass media for the conservation of their culture. Some of the key issues that I’ll be discussing are related to the role of the Other in the process of the construction of the knowledge and the authenticity of the indigenous films, the legitimacy of postcolonial ethnographic film as an ethnographic document, methodologies of self-representation and the relationship between the anthropologist/filmmaker and the Other. The Other in postcolonial ethnographic film is no longer a passive object of ethnographic representation but an active participant and the creator of the filmic representation. The deconstruction of the dominant Eurocentric discourse was further enhanced by the appearance of new voices, new gazes and different knowledge have enriched the contemporary ethnographic film.
Projekt MZOS
ENG